Transient Myeloproliferative Disorder in a Neonate without Down Syndrome—A Rare Case Report and Review of the Literature - Devaki Menon Kizhakke Vellatt; Dhaarani Jayaraman; Shwetha Amuthan; Umamaheswari Balakrishnan; Teena Koshy; Arun Kumar Subramanian; Julius Xavier Scott (Indian Journal of Medical and Paediatric Oncology)
Transient myeloproliferative disorder (TMD) is a self-limiting disorder characteristically seen in neonates with Down syndrome with or without somatic mosaicism. Trisomy-21 limited to the hematopoietic lineage alone has been described; awareness of which is very important for appropriate evaluation and counseling in phenotypically normal children.